2012
DOI: 10.1002/anie.201205115
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Enantioselective Cobalt‐Catalyzed Reductive [3+2] Cycloaddition Reaction of Alkynes with Cyclic Enones: A Route to Bicyclic Tertiary Alcohols

Abstract: Round and round: An unusual cobalt-catalyzed regio- and enantioselective reductive [3+2] cycloaddition of cyclic enones with alkynes affording bicyclic tertiary alcohols is described. A possible mechanism involving the formation of a cobaltacyclopentene intermediate is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Ther eaction proceeds well either with abulky OTBS or with an unprotected hydroxyl moiety at the propargylic position, so that 2cand 2d were obtained in almost identical er and yields. Likewise,the cycloaddition of precursor 1e,bearing an O-allyl group,w as also efficient and gave 2e in 13-t oluene 31 10 66 [b] 2P d 2 dba 3 (6) L2 13-t oluene 16 110 12 3R h(COD)Cl] 2 (10) P(OPh) 3 (12) -t oluene 20 110 -4R hClCO(PPh 3 ) 2 (10) --toluene 20 110 -5R hCl(PPh 3 ) 3 (10) --toluene 20 110 -6N i(COD) 2 (10) --toluene 12 110 -7C oBr 2 (10) dppp 12 (10) dppp 12Zn [d] CH 3 CN 31 00 24 9C oBr 2 (10) dppp 12In [d] CH 3 CN 31 00 82 10 CoBr 2 (10) dppp (12) In/InI [20] the use of at erminal alkyne as ac ycloaddition partner is also tolerated. Thus,precursor 1fwas efficiently transformed into its corresponding cycloadduct, 2f,i n7 2% yield, and with an excellent 95:5 er.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ther eaction proceeds well either with abulky OTBS or with an unprotected hydroxyl moiety at the propargylic position, so that 2cand 2d were obtained in almost identical er and yields. Likewise,the cycloaddition of precursor 1e,bearing an O-allyl group,w as also efficient and gave 2e in 13-t oluene 31 10 66 [b] 2P d 2 dba 3 (6) L2 13-t oluene 16 110 12 3R h(COD)Cl] 2 (10) P(OPh) 3 (12) -t oluene 20 110 -4R hClCO(PPh 3 ) 2 (10) --toluene 20 110 -5R hCl(PPh 3 ) 3 (10) --toluene 20 110 -6N i(COD) 2 (10) --toluene 12 110 -7C oBr 2 (10) dppp 12 (10) dppp 12Zn [d] CH 3 CN 31 00 24 9C oBr 2 (10) dppp 12In [d] CH 3 CN 31 00 82 10 CoBr 2 (10) dppp (12) In/InI [20] the use of at erminal alkyne as ac ycloaddition partner is also tolerated. Thus,precursor 1fwas efficiently transformed into its corresponding cycloadduct, 2f,i n7 2% yield, and with an excellent 95:5 er.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Moreover,italso constitutes one of the very few asymmetric (3+ +2) annulations promoted by cobalt reagents. [10] Them ethod provides as traightforward approach to fivemembered fused bicyclics caffolds (2)f rom simple,r eadily accessible ACPp recursors (1,S cheme 1b). [11] Remarkably, we have found that the performance of the Co catalysts is much superior to that of Pd or Rh alternatives.W ea lso demonstrate that asimple hydrogenation protocol allows the stereospecific transformation of the adducts into enantioenriched fused-bicarbocyclic systems bearing up to four stereocenters.I mportantly,w ei nclude experimental and computational results that allow us to propose aC o I /Co III catalytic cycle encompassing cobaltacyclopentene and p-allyl cobalt intermediates and shed light into the origin of the enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when the reaction of internal alkynes and cyclopentenone or cyclohexenone was performed under slightly modified conditions (Scheme 17) in the absence of water, the reaction pathway could be modified. 40 In the presence of CoBr 2 /dppe/Mn/ZnCl 2 in acetonitrile or CoI 2 / ligand/Zn/ZnI 2 in 1,4-dioxane, the transformation led to a [3+2] cycloaddition and in the presence of a chiral ligand such as (R,R,S,S)-Duanphos, bicyclic products such as 25 were formed in good yields and moderate to excellent enantioselectivities depending on the ring size and the substitution pattern of the enone starting material.…”
Section: Scheme 16mentioning
confidence: 99%
“…Based on the studies on reductive coupling of alkynes with cyclic enones to β-substituted ketones, 23 a nonasymmetric Co-catalyzed reductive [3+2] cycloaddition of cyclic enones and alkynes using CoI 2 /dppe, Mn, and ZnCl 2 was discovered. 24 Bicyclic tertiary alcohols afforded the products with good to high regioselectivity. Having successfully established reductive [3+2] cycloaddition reaction OH n conditions, DuanPhos was found to be the most efficient chiral phosphine ligand to ensure both high regioselectivity and high enantioselectivity (up to >99% ee).…”
Section: Co-catalyzed Reductive [3+2] Cycloaddition Reactionmentioning
confidence: 99%
“…Having successfully established reductive [3+2] cycloaddition reaction OH n conditions, DuanPhos was found to be the most efficient chiral phosphine ligand to ensure both high regioselectivity and high enantioselectivity (up to >99% ee). 24 The reductive [3+2] cycloaddition with Co-DuanPhos catalyst successfully converted various aromatic alkynes with cyclic enones to the bicyclic products with excellent enantioselectivity and in good yields (Table 7). Alkynes bearing both phenyl and substituted phenyl groups afforded excellent ee values (90-99% ee) ( Table 7, entries 1-4).…”
Section: Co-catalyzed Reductive [3+2] Cycloaddition Reactionmentioning
confidence: 99%